Executive and independent regulations:a obsolete distinction to determine the intervention of the Council of State? - Quereda Sabater, Juan (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
This article analyzes, firstly, the attempts of the Supreme Court ("Tribunal Supremo") to define concepts of executive and independent regulation.This delimitation is essential to determine which normative projects should be sent to the Council of State ("Consejo de Estado") and equivalent regional bodies. Although we consider that the Supreme Court has not managed to delimit these concepts in a precise and coherent way, we also observe that, since the approval of Organic Law 3/1980, of April 22, of the Council of State, there has been a significant increase the type of regulatory projects that are sent to these bodies. This increase is due both to the expansion in jurisprudence of the concept of executive regulation, to a parallel reduction of the concepts of independent and organizational regulation and to the increase in state and autonomous legislative activity. This increase, which we value positively from the point of view of normative quality, is, however, a still incomplete expansion, which leaves numerous normative projects of unquestionable importance without the advice of the Council of State or regional consultative bodies. We propose, as an alternative to the current system, a simpler delimitation criterion, of a mainly formal nature, which would make it mandatory to refer all regulatory projects to these bodies.
Keywords: Elaboration of norms and regulations; normative quality; executive and independent regulations; Council of State; autonomous advisory bodies